Occurrence of urea-based soluble epoxide hydrolase inhibitors from the plants in the order Brassicales. - Seiya Kitamura; Christophe Morisseau; Todd R Harris; Bora Inceoglu; Bruce D Hammock (PLoS ONE)
Recently, dibenzylurea-based potent soluble epoxide hydrolase (sEH) inhibitors were identified in Pentadiplandra brazzeana, a plant in the order Brassicales. In an effort to generalize the concept, we hypothesized that plants that produce benzyl glucosinolates and corresponding isothiocyanates also produce these dibenzylurea derivatives. Our overall aim here was to examine the occurrence of urea derivatives in Brassicales, hoping to find biologically active urea derivatives from plants. First, plants in the order Brassicales were analyzed for the presence of 1, 3-dibenzylurea (compound 1), showing that three additional plants in the order Brassicales produce the urea derivatives. Based on the hypothesis, three dibenzylurea derivatives with sEH inhibitory activity were isolated from maca (Lepidium meyenii) roots. Topical application of one of the identified compounds (compound 3, human sEH IC50 = 222 nM) effectively reduced pain in rat inflammatory pain model, and this compound was bioavailable after oral administration in mice. The biosynthetic pathway of these urea derivatives was investigated using papaya (Carica papaya) seed as a model system. Finally, a small collection of plants from the Brassicales order was grown, collected, extracted and screened for sEH inhibitory activity. Results show that several plants of the Brassicales order could be potential sources of urea-based sEH inhibitors.